The Use Of The Two Stay Two Stray (TS -TS) Strategy To Improve Students' Speaking Ability Of The Grade Eight In SMPN 5 Padang Panjang - Hendrita, Rini; Cahyani, Indah Gita; syam, Erlinda (Inovasi Pendidikan, 2025)
This research aims to investigate the effectiveness of the Two Stay Two Stray (TSTS) strategy in improving the speaking skills of eighth-grade students at SMPN 5 Padang Panjang. This study employed a pre-experimental design with a one-group pre-test and post-test. The sample consisted of 20 students selected randomly from a total of 32 students. The instruments used were speaking tests (pre-test and post-test). The findings revealed that the students’ post-test scores were higher than their pre-test scores. A t-test with a degree of freedom (df) = 19 resulted in t-count = 10.78, while the t-table at the 0.05 significance level was 2.093. Since t-count t-table, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, indicating a significant difference between pre-test and post-test results. Therefore, it can be concluded that the implementation of the Two Stay Two Stray (TSTS) strategy is effective in improving students’ speaking skills at SMPN 5 Padang Panjang. Keywords : Two Stay Two Stray Strategy, Speaking Skill, Cooperative Learning Strategy